The existence of the community of historical interest in the effort of preserving the cultural conservation of Malang City - Irwan Yulianto; Estikowati Estikowati (Universitas Merdeka Malang, 2022)
The heritage left in Malang City is very diverse, one example is cultural heritage but public ignorance about the existence of cultural heritage in Malang City such as buildings and historical events introducing Malang City cultural heritage to the public and tourists in a light and educative way, namely historical tourism. The History Enthusiast Community is one of the associations concerned with saving history that is serious about organizing historical tours, the Malang Old Photo community carries the theme Mbloesoekan en Djagongan every month holding activities with the aim of informing all people about historical zones in Malang City and outside Malang City. The introduction of historical zones to the community consisting of millennials is routinely carried out considering vandalism against cultural heritage buildings in Malang is still rampant. The activity of the history enthusiast group in broadcasting the historical zone gave researchers ideas to find out the process of delivering the material used in history enthusiast activities, as well as knowing the existence of the History Enthusiast Community in preserving the cultural heritage of Malang City. The method used is a qualitative method through data collection techniques such as exploration, conducting questions and answers, and documentation. As for the results and discussion, the process of delivering materials used in the History Enthusiast Community is the delivery of materials, panel discussions, and building tours. The existence of History Enthusiast Community in maintaining cultural heritage in Malang City by conducting an inventory of cultural heritage by matching photos uploaded on Instagram to save buildings, and publications.